Building knowledge to ease troublesomeness: Affording theory knowledgeability through academic reading circles - Cowley-Haselden, Susie (Journal of University Teaching and Learning Practice, 2020)
Academic reading for knowledge building is under-researched in the field of English for Academic Purposes (EAP); a field that foregrounds academic writing above all other skills. Alongside this dearth of literature, a relative wealth of literature exists which identifies the ‘troublesomeness’ of academic reading. This paper argues that reading for knowledge building is one way to ease the troublesomeness of academic reading within the field of EAP, with a focus on reading to build knowledge of theory and theory use. This paper reports on findings from a study which explores how taught postgraduates on a pre-sessional course acquire the threshold concept of ‘theory knowledgeability’ (Cowley-Haselden 2020) through reading and discussion. ‘Theory knowledgeability’ can be defined as not just acquiring knowledge of how to use theory in academic practice, but also acquiring knowledge of particular theory/ theories themselves. This knowledge is one key to unlocking success in postgraduate level education. Through the analysis of knowledge practices within academic reading circles performed by postgraduate pre-sessional students from a range of disciplines within the social sciences, it is argued that acquiring the threshold concept of theory knowledgeability allows students to emerge as a more legitimate knower in the UK higher education context.